ASSOCIATION BETWEEN PARAFOVEAL CAPILLARY NONPERFUSION AND MACULAR FUNCTION IN EYES WITH BRANCH RETINAL VEIN OCCLUSION. Issue 9 (September 2017) - Manabe, Saki; Osaka, Rie; Nakano, Yuki; Takasago, Yukari; Fujita, Tomoyoshi; Shiragami, Chieko; Hirooka, Kazuyuki; Muraoka, Yuki; Tsujikawa, Akitaka
Abstract : Purpose: To investigate the parafoveal perfusion status of the superficial and deep capillary layer in eyes with resolved branch retinal vein occlusion, and to study its effects on retinal sensitivity. Methods: In 27 enrolled eyes (27 patients) with resolved branch retinal vein occlusion, superficial and deep capillaries in the macular area (3- × 3-mm, centered on the fovea) were examined with optical coherence tomography angiography. Retinal sensitivity was examined with fundus-monitored microperimetry. Results: Optical coherence tomography angiography clearly showed the parafoveal superficial and deep capillaries individually. On the affected side of retina, 25 eyes (92.6%) showed capillary nonperfusion; 23 (85.2%) in the superficial layer and 22 (81.5%) in the deep layer. Capillary nonperfusions of both layers frequently overlapped and appeared to be connected with each other. Mean (±SD) retinal sensitivity at the superficial capillary nonperfusion was 19.2 ± 6.3 dB, significantly lower than that at the superficial capillary perfusion (24.4 ± 2.8 dB, P < 0.001). Similarly, mean retinal sensitivity at the deep capillary nonperfusion was 20.8 ± 5.0 dB, significantly lower than that at deep capillary perfusion (24.3 ± 2.8 dB, P = 0.0016). Mean retinal sensitivity with superficial capillary nonperfusion was significantly lower than that with deep capillary nonperfusion ( P = 0.0226). Conclusion: Optical coherence tomography angiography visualized parafoveal capillary nonperfusion in superficial and deep layers individually in eyes with resolved branch retinal vein occlusion. Retinal sensitivity was significantly reduced at these capillary nonperfusions. Abstract : Optical coherence tomography angiography visualized parafoveal capillary nonperfusion in superficial and deep layers individually in eyes with resolved branch retinal vein occlusion. Retinal sensitivity was significantly reduced at these capillary nonperfusions.